Segmentation of Paddy Fields from A Remote Sensing Images Using Ai Based Learning - Kumar, Rajiv; Maheshwari, Shikha; Prasad, J. Rajendra; Moharana, Rajeeb Lochan; Sarvani, Chalamalasetty; Babu P., Ramesh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Hyperspectral image segmentation (HSI) is a technique that is commonly used to remove redundant and linked data from the original high-dimensional HSI spectral space while at the same time keeping the essential data in a low-dimensional subspace. The use of superpixels has been beneficial to a wide variety of applications, some of which are listed here. In this paper, for the very first time, zeroed in on how well-established super-pixel techniques can serve as a helpful first stage in hyperspectral analysis, with a concentration on classification. In addition to this, we make use of the network that is in the middle of the model, and after that, we employ the technique known as feature fusion to combine the features that originate from the various subnetworks.